The Relation between the Positive Stool Antigen of Helicobacter Pylori with Iron Deficiency Anemia in (6-14) Years old Children - شريتح أحمد; زعبلاوي يوسف; شعبان ضحى (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Helicobacter pylori (H.P) infection is considered as one of the most common chronic bacterial infections around the world. Its prevalence rate is estimated at 44.3%, with an increasing rate about 50.8% in the developing countries compared to the rate in developed countries which is about 34.5%. The H.P infection may cause iron deficiency anemia. Objective: The relation of H.P infection with iron deficiency anemia among children with signs of anemia at the ages between 6 to 14 years old. Methods: an observational descriptive cross-sectional study was conducted. The study included 150 children of (6 to 14) years old that have suggestive signs of anemia. 15 cases were excluded (7 cases with antibiotics therapy, and 8 with iron therapy). A CBC was performed for each child to determine the presence of anemia, and the stool antigen of helicobacter pylori was investigated to diagnose the infection. Results: The number of patients in the study reached (135) children (80 male, 55 female). The average age was 9.2 ± 2.2 years. The number of children infected with anemia is 68 children, or 50.4% rate. The positive rate of stool antigen with anemia was (32%) with p-value<0.01. The age group (9-12) years represented 50% of infected children with anemia with a positive stool antigen of H.P. Conclusion: The study found an important relation between H. pylori infection and iron deficiency anemia, where anemia was more pronounced in children infected with H. pylori compared to the non-infected.